Antidrug antibodies in psoriasis: a systematic review. (1st February 2014) - Hsu, L.; Snodgrass, B.T.; Armstrong, A.W.
Summary: Antidrug antibodies (ADAs) against biological agents may be clinically significant and potentially alter a biological drug's treatment efficacy. This systematic review aims to (i) determine the prevalence of ADAs against infliximab, etanercept, adalimumab and ustekinumab in patients with psoriasis; (ii) ascertain whether ADAs are associated with changes in drug efficacy; and (iii) explore the use of concomitant methotrexate to prevent ADA formation. Through a systematic search using Medline and Embase from 29 January 1950 to 29 March 2013, we identified 25 studies that met the inclusion criteria. Of 7969 patients with psoriasis, 950 tested positive for ADAs. Antibodies against infliximab, etanercept, adalimumab and ustekinumab were reported in 5·4–43·6%, 0–18·3%, 6–45% and 3·8–6% of patients, respectively. Anti‐infliximab antibodies were associated with lower serum infliximab concentrations in three studies, and decreased treatment response in five studies. ADAs against etanercept were non‐neutralizing and not associated with any apparent effects on clinical response. Antiadalimumab antibodies were associated with lower serum adalimumab concentrations in three of five studies, and reduced clinical efficacy in four studies. Two of six studies reported that antiustekinumab antibodies were associated with lower Psoriasis Area and Severity Index responses, and three ustekinumab studies noted that most of these antibodies were neutralizing. Although the use of concomitant methotrexate with biological agents to prevent ADA formation in other immune‐mediated diseases is promising, their use in psoriasis is sparse. ADA development remains a challenge with biological therapies and therefore should be considered in patients with psoriasis who experience diminished treatment response.